A comparative study of endotracheal tube cuff pressure changes in patients undergoing open abdominal and laparoscopic surgeries - Shanmugavalli Ettiyan,; Jayabal, Hari Babu; Chandrasekaran, Rajesh Prabhu (Asian Journal of Medical Sciences, 2024)
Background: Laparoscopic surgeries are routinely performed because it’s minimally invasive and early recovery for patients. The preferred mode of anesthesia is general anesthesia with an endotracheal tube (ETT). The creation of the pneumoperitoneum and various positions cause cuff pressure (CP) changes. Aims and Objectives: We aim to study the CP changes and post-operative complications related to it. The secondary objective was to observe the post-operative complications such as sore throat, hoarseness of voice, and blood-streaked expectoration after extubation at 12 h, and at the time of discharge from the post-anesthesia care unit. Materials and Methods: One hundred and fifty patients undergoing elective open abdominal and laparoscopic surgeries were enrolled. Three groups (open abdominal [group A], n=50; lap head up [group B], n=50; and lap head down [group C], n=50) were compared for CP changes before and after pneumoperitoneum and position change. CP changes and post-operative complications were recorded and analyzed with Statistical Package for the Social Sciences version 19. Results: Mean differences in CP after intubation at 5 min were similar in all three groups. At 45 min onward, the mean CP in group C was found to be elevated and continued to increase till the end of surgery. However, at 90 min, group B also showed some increase in CP. There was a mild increase in CP in groups B and A. The mean difference between groups was found to be remarkable. During the post-operative period, there were 0.7% and 3.3% of cases with throat pain in group B and group C, and 2% of patients in group C had blood streak expectoration. Conclusion: In laparoscopic surgery, especially in a head-down position, a considerable increase in CP is associated with postoperative complications.